Study of changes in Flow Volume curves in obese middle-aged individuals with obstructive pulmonary disease - C. Anithu; C.P. Ganashree; R. Rajalakshmi (Al Ameen Medical College, 2013)
Objective: To study the effect of obesity on Flow Volume curves of middle aged individuals with obstructive pulmonary disease. Background: Obesity and obstructive pulmonary disease quite often co-exist in the same individual seeking treatment for respiratory illness. Not many studies have been done about the impact of obesity on dynamic respiratory mechanics in patients with obstructive lung disease in South India. Materials & Methods: This is a retrospective cross sectional study where data was collected from the Department of Pulmonary Medicine, JSS hospital, Mysore. 120 normotensive non diabetic subjects in the age group of 40-60 years, were divided into four groups based on their BMI and the presence of obstructive findings. Flow Volume loop, FEV1, FVC and FEV1/ FVC were recorded using computerised spirometer. Results: The measured FEV1/FVC % in obese patients with obstructive findings was significantly lower than in normal BMI patients with obstructive findings. Obese individuals without obstructive findings also showed significantly lower measured FEV1/FVC % than normal BMI individuals without obstructive findings. Conclusion: Obese individuals have more obstruction when compared to even normal BMI individuals with symptoms. As the changes in respiratory mechanics due to obesity are almost completely reversible, early intervention in obese patients with COPD will ensure lower dependence on medicines to manage the respiratory condition.